Chemo-poroplastic analysis of a borehole drilled in a naturally fractured chemically active formation - Roshan, H.; Fahad, M. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2012)
A coupled chemo-poroplastic model is developed to investigate the change in ion transfer and its effect on pore pressure and effective stresses in chemically active fractured media. The equivalent permeability tensors are calculated using the boundary element method for an arbitrary oriented fractured system, and used in the chemo-poroplastic model. An explicit modified Euler algorithm with substepping including a yield surface correction scheme is used to integrate the plastic stress–strain relation. Super-convergent patch recovery method is also used to accurately evaluate the time dependent nodal stress tensors from the stress tensors of gauss points. From the results of this study it was revealed that the pore pressure drops around the wellbore due to chemical osmotic back flow. The drop in pore pressure, however, becomes a function of fractures' orientation and density. The state of stresses reach the yield strength of the rock in fractured shale, thus forming a plastic zone around the wellbore. The relaxation of effective tangential stresses in the plastic zone, therefore, has a potential to cause stability problems. ► We modelled the chemo-poroplastic behaviour of a naturally fractured shale using FEM. ► We efficiently calculated permeability tensors for a shale fractured system using BEM. ► The change in solute transfer, pore pressure and stresses were analysed. ► Solute transfer and pore pressure were significantly altered in presence of fractures. ► The plastic deformation occurred in fractured shale but not in homogeneous shale.